2010
DOI: 10.1088/1742-5468/2010/10/p10014
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric simple exclusion process on a Cayley tree

Abstract: We study the asymmetric exclusion process on a regular Cayley tree with arbitrary co-ordination number. In this model particles can enter the system only at the parent site and exit from one of the sites at the last level. In the bulk they move from the occupied sites to one of their unoccupied downward neighbours, chosen randomly. We show that the steady state current that flow from one level to the next is independent of the exit rate, and increase monotonically with the entry rate and the co-ordination numb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…(9) it follows that either ρ (2,3) bulk = ρ − (1/8) 0.146 and the defect chains C 2,3 are in the LD phase or ρ (2,3) bulk = ρ + (1/8) 0.854 and the defect chains C 2,3 are in the HD phase.…”
Section: A Mean-field Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…(9) it follows that either ρ (2,3) bulk = ρ − (1/8) 0.146 and the defect chains C 2,3 are in the LD phase or ρ (2,3) bulk = ρ + (1/8) 0.854 and the defect chains C 2,3 are in the HD phase.…”
Section: A Mean-field Theorymentioning
confidence: 99%
“…The values of α * d and β * d are calculated from the finite-size numerical data for the local densities τ (1) L 1 , τ (4) 1 , τ (2,3) 1 and τ (2,3) L d using Eqs. (5) and (6) with J L = J MC = 1/4.…”
Section: A Mean-field Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…These systems allow additional motion of particles in the TASEPs and can be interpreted as networks of TASEPs and reservoirs, where each site in a lattice is connected with the particle reservoir or a site in a different TASEP. On the other hand, the TASEP on networks has been focused on recently [16][17][18][19]. The results have concluded that the dynamics of the system depends on structure of the networks.…”
Section: Introductionmentioning
confidence: 99%
“…However, very little analysis has been carried out for the transport of packets in tree-or river-like branching hierarchical networks [30]. In this paper, we explore the transport dynamics and statistics on a hierarchical regular 2D lattice model, two of its variants [31], and its critical case [32].…”
Section: Introductionmentioning
confidence: 99%